Objective evaluation of caudal deviation of the nasal septum and selection of the appropriate septoplasty technique. Issue 1 (February 2022) - Kimura, Shogo; Suzuki, Masanobu; Honma, Aya; Nakazono, Akira; Osawa, Masayuki; Nakamaru, Yuji; Homma, Akihiro
Abstract: Objective: Several methods have been reported to correct caudal deviation of the nasal septum, including open septorhinoplasty (OSR) and septoplasty with Killian incision (KI). In general, OSR is applied instead of KI for caudal deviation. However, there is little objective evidence own on the effects of OSR and KI for caudal deviation. In this study, we compared surgical outcomes between OSR and KI by quantifying nasal septum deviation using two simple and objective parameters on routine paranasal sinus CT scans. Methods: We retrospectively analyzed 18 patients who underwent OSR and 11 patients who underwent septoplasty with KI between April 2006 and October 2019. Caudal deviation was defined on the basis of the "Anterior-posterior Position of the most deviated point of the nasal septum (AP), " which was measured on computerized tomography. The deformation rate (DR) of the nasal septum was also calculated. Nasal airway resistance and visual analogue scale (VAS) score for nasal obstruction were examined. Results: The AP was significantly correlated with the VAS score (r=-0.58, p=0.017). The DR in patients with caudal septal deviation was significantly decreased by OSR (0.14±0.06 to 0.03±0.03, p=0.004), but not by KI (0.09±0.08 to 0.04±0.03, p=0.25). OSR also improved nasal airway resistance (1.10±0.44 to 0.42±0.15, p=0.02), and the VAS score (79.11±14.74 to 5.78±7.89, p=0.004). Conclusion: Nasal obstruction is more severe in patients with the caudal deviation. OSR corrects caudal deviation of the nasal septum more effectively than does KI. The AP could be useful for the evaluation of the deviation of the nasal septum and help in selecting the appropriate septoplastic technique.